Peningkatan Hasil Belajar Pendidikan Pancasila Materi Norma Dalam Kehidupanku Menggunakan Media Pembelajaran Wordwall Kelas V SDN 007 Samarinda Ilir - Utami; Iksam; Taufik Hidayat; Sukriadi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study was motivated by the low learning outcomes of fifth-grade students at SDN 007 Samarinda Ilir, particularly in the subject of Pancasila Education. The purpose of this study was to improve students’ learning outcomes in Pancasila Education on the topic Norms in My Daily Life through the use of Wordwall learning media for fifth-grade students at SDN 007 Samarinda Ilir in the 2025/2026 academic year. This research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of two meetings. The research process followed four stages: planning, implementation, observation, and reflection. The research subjects were 28 fifth-grade students of SDN 007 Samarinda Ilir, while the object of the study was students’ learning outcomes in Pancasila Education. Data collection techniques included observation, testing, and documentation. The instruments used were teacher activity observation sheets, student activity observation sheets, and evaluation tests. Data analysis techniques involved calculating averages, percentages, and graphical representations. The results showed an improvement in students’ average scores from the pre-cycle stage, which was 62.1 with a mastery percentage of 39% (very low category). In Cycle I, students’ learning outcomes increased by 16.16% from the pre-cycle baseline, with an average score of 72.14 and a mastery percentage of 61%. In Cycle II, learning outcomes increased by 24.79% from the pre-cycle baseline, achieving an average score of 77.5 with a mastery percentage of 82%, where 23 students achieved mastery and 5 students did not. This result exceeded the predetermined success indicator of 75%. Based on these findings, it can be concluded that the use of Wordwall learning media effectively improves learning outcomes in Pancasila Education on the topic Norms in My Daily Life for fifth-grade students at SDN 007 Samarinda Ilir in the 2025/2026 academic year.